Desenvolvimento de uma ferramenta de apoio aplicada à gerência de acidentes de trânsito - Souza, Adilso Nunes de (2015)
The increase rate in the motor vehicle fleet has grown considerably in recent decades, mainly due to urbanization and ease of car ownership, which engenders several problems for traffic, such as traffic jams and accidents. In most municipalities, the lack of information that characterizes the traffic complicates the implementation of actions and projects to improve flow and reduce accidents on the roads. Thus, this study sought to improve the knowledge of how to collect and store detailed data on traffic accidents by developing a computerized application, accessed by mobile devices through the Internet. This collection of data is performed by the professionals working in traffic surveillance in the city of Passo Fundo, upon occurrence. All information is then pooled and stored in a single database. The developed system provided reevaluate and expand the information collected by organizing the registration process and providing different ways of viewing information in statistical reports, to be used as survey information and promote the information research and assist authorities in the decision-making process, in its different aspects: whether in making investments in road infrastructure, such as readjustments to provide greater agility and safety for users, among other measures, helping to make traffic better